1986
DOI: 10.1126/science.233.4770.1311
|View full text |Cite
|
Sign up to set email alerts
|

Bacterivory: A Novel Feeding Mode for Asteroid Larvae

Abstract: Planktotrophic larvae that occur beneath the annual sea ice in the Antarctic assimilate organic solutes and preferentially ingest bacteria, whereas they actively exclude phytoplankton. In regions where phytoplankton biomass is temporally limited by light or nutrient concentrations, the growth and development of planktotrophic larvae may not be directly coupled to phytoplankton production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…Bacteria, the focus of the present study, are ingested and assimilated by certain echinoderm larvae (Rivkin et al 1986, Pearse et al 1991 and by bivalve larvae (Chalermwat et al 1991, Douillet 1993a.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Bacteria, the focus of the present study, are ingested and assimilated by certain echinoderm larvae (Rivkin et al 1986, Pearse et al 1991 and by bivalve larvae (Chalermwat et al 1991, Douillet 1993a.…”
Section: Introductionmentioning
confidence: 90%
“…Since planktotrophic larvae in many regions may encounter phytoplankton abundances that are insufficient to sustain survival and growth, bacteria have been suggested as a supplementary source of organic matter (Crisp et al 1985, Rivkin et al 1986, Olson 1987, Douillet & Langdon 1993 and nutrients (Phillips 1984, Baldwin & Newel1 1995. This hypothesis is supported by studies showing that bivalve larvae can obtain enough energy through bacterivory to meet a portion of a larva's metabolic needs (Chalermwat et al 1991, Douillet 1993b, and that growth and survival are enhanced when certain strains of bacteria are added to phytoplankton cultures used to feed larvae (Martin & Mengus 1977, Douillet & Langdon 1993.…”
Section: Introductionmentioning
confidence: 99%
“…These data, in conjunction with mounting evidence that food limitation may not be an important aspect of plankton-feeding larvae in the antarctic (where phytoplankton levels are much lower than on coral reefs) (Olson et al 1987;Rivkin et al 1986), indicate that year-to-year fluctuations in larval food levels may explain an insignificant amount of variation in interannual recruitment ofA. planci.…”
Section: Discussionmentioning
confidence: 50%
“…Manahan et al (1983) suggested that the larvae of an echinoid could obtain up to 79% of their energetic needs from uptake of DOM. Rivkin et al (1986) have shown that bacteria may be a major source of nutrition for the larvae of some Antarctic asteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria are an important component of the microbial loop (Azam et al 1983). A variety of aquatic animals, common or dominant in their communities, have been shown to effectively capture bacteria in addition to other planktonic food (e.g., acleractinian coral, Bak et al 1998; reef sponges, Reiswig 1974, Pile 1997; polychaete larvae and juveniles, Gosselin & Qian 1997mussels, Seiderer & Newell 1985, Langdon & Newell 1990, Kreeger & Newell 1996 clams, Decho & Luoma 1991; oyster larvae and adults, Langdon & Newell 1990, Douillet 1993, Douillet & Langdon 1993; asteroid larvae, Rivkin et al 1986;and ascidians, Bak et al 1998). These studies have pointed out the significance of bacteria as a carbon source for the animal nutrition.…”
Section: Introductionmentioning
confidence: 99%